Adapting, modifying and applying cinematography and editing concepts and techniques to cinematic virtual reality film production. Issue 1 (February 2023) - Zhang, Yu; Weber, Ian
Virtual reality (VR) filmmaking presents a unique cinematic experience requiring new and innovative ways to conceptualise and practice specific aspects of the production process. This article integrates a range of adapted and modified filmmaking thinking, approaches and components into the cinematic virtual reality (CVR) language and grammar in the two critical areas of cinematography and editing. This focus provides a range of possible strategies and tools for would-be VR film directors to engage more efficiently and effectively in VR film production. The article utilises an extended case study of the VR feature film Calling to present the director/editor's observations and experiences using transmedia journaling and three-dimensional (3D) CVR previsualisation as a simulation tool to create this dynamic, interactive CVR film.